Development of a Device for Continuously Monitoring the Parameters of the Winding Structure of Textile Bobbins (2018)
Introduction: The research “Improving the control methods for winding structure at friction drive machines” was conducted at Azerbaijan State Economic University in 2017. Methods: To assess the efficiency of the proposed technique for processing signals, a model of a WA device, which allowsthe unwinding of the package, was designed and manufactured. Results: The authors developed a methodology and a corresponding device to quantitatively assess the parameters of the winding structure by the light-section method. Conclusions: The dimensions adopted while designing the device make it possible to exclude the influence of the non-roundness of the bobbin on the measurement results. Originality:  The equipment advancement and quality control improvement are the most urgent issues in textile industry. The quality requirements for package is constantly growing, while this research contribute to maintain it at a corresponding level, which ensures further development of textile industry as a whole. Limitations: The research results can be practically implemented in new winding motion design for spinning frames with cross-winding bobbin.